The role of tea in cardiovascular disease - Gunawijaya, Fajar Arifin (Universa Medicina, 2008)
Tea is an infusion of the leaves of the Camellia sinensis plant, which is not to be confused with so-called âherbalâ teas. Some biologically active chemicals in tea include flavonoids, caffeine and fluoride. For as long as people have been drinking tea, there have been health benefits associated with it. However, it has only been within the past 20 to 30 years that scientific studies have been conducted to investigate the validity of these claims. Many animal studies, and recently an increasing number of human studies, including epidemiological studies and clinical trials, have examined the relationship between tea drinking and health. Overall, observational studies in humans suggest that daily consumption of at least 3 cups of tea may be associated with a risk reduction of mortality (44%) after myocardial infarction compared with non-tea drinkers. The possibility that tea consumption reduces the risk of cardiovascular events remains open to the need for further clinical trials to clarify the effects of tea polyphenols in humans in order to recommend their use against cardiovascular diseases.